Observing pro-environmental behavior based on consumer attitudes and norms - Jati Waskito; I Imronudin; C Chuzaimah (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2019)
This study aims to investigate the differences in underlying psychological aspects regarding pro-environmental behavior between two distinct consumer groups: green product and non-green product consumers. Psychological aspects investigated includes cognitive attitude, affective attitude, social norm, and behavioral intention. Using survey, a total of 276 responses from Solo, Jogyakarta, and Semarang are succesfully collected. Confirmatory factor analysis was conducted to check the measurement model, while a multiple regression and MANOVA were performed to examine the proposed hypothesis. Compared to non-green product consumers, green product consumers exhibited significantly higher levels of cognitive attitude, affective attitude, social norm, personal norm, and green consumer behavior. Also cognitive, affective attitude, and personal norm predicted green consumer behavior. The limitations of this study include the self-reporting questionnare and the measurmenet of consumers’ recycling intention rather than their actual behavior.